Privacy and personal data protection in electronic voting : Indonesia case study - Lubis, Muharman (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
The wide-ranging adoption of technology over recent years has provided tremendous benefits to society in nearly all fields of human activity – be it in scientific and academic research, entertainment, finances, genetics, archiving, communication, or political election. Despite this promising development, every innovation possesses its own advantages and disadvantages and merits careful evaluation – such as in terms of ethical and normative standards, possible exposure to crime-related material, environmental impact, censorship issues, health-related effects, excessive dependability and the most crucial of all – privacy violation. In general, the process of electronic voting or as commonly known as e-voting, offers the opportunity to reduce the time and budget needed for its implementation which makes e-voting more attractive rather than traditional approach. Certain aspects of the process may positively or negatively signify the influence of execution. Considering the gaps in academic literature and its importance to analysing privacy protection in the context of e-voting, this study used mixed research using the triangulation method including survey, content analysis and interview with threefold purpose. Firstly, it seeks to investigate if the extent of personal data protection is correlated with technology, legal and social factors through privacy concerns and perceived benefits. Secondly, it seeks to establish the privacy framework based on nature of election that aligns with the mutual comprehension of relevant factors. Thirdly, it seeks to predict the element that plays the key role in determining the performance quality of e-voting. A total of 790 eligible voters (431 males and 348 females) were drawn from critical case of purposive sampling. Three instruments were developed to collect data; self-developed checklist of coding paper, structured interview and questionnaire. The findings indicated that concern of privacy have positive influence towards personal data protection, especially by utilizing technology solution in electronic voting. Some attributes supports the privacy protection like ease of access, biometric use, access control and identification. Meanwhile, legal has weak significance over concern of privacy but it has no significance for perceived benefits. Moreover, 21 coders have agreed that respective regulation have moderate role of privacy protection in electronic voting while majority experts recommend verbally to government and electoral commission to do more socialization about e-voting initiative. These result demonstrate that the proposed framework can be developed further in achieving the objective of this study.